Chest Radiograph appearance of SARS-Cov-2 Infection: A Prospective Observational Study of Ambulatory Patients from a Field Hospital in a Middle-Income Country (Journal of Fatima Jinnah Medical University, 2023)
Background: The ongoing COVID-19 pandemic has had a profound impact on both individuals and society, resulting in widespread illness and death, as well as a global economic downturn. In order to examine chest X-rays (CXRs) of ambulatory patients diagnosed with COVID-19 in a field isolation center, our aim is to determine the proportion of patients with normal versus abnormal chest radiographs. Moreover, in cases where abnormal findings are present on the CXR, our goal is to document the distribution and patterns of these abnormalities.Method: This prospective observational study was conducted on a cohort of 510 consecutive COVID-19 patients who tested positive for the virus and presented at the field isolation center between March 15th and May 15th, 2020. The study encompassed patients of all ages and both genders, with the exclusion criteria being patients requiring intensive care and those with unreadable CXRs due to technical limitations. The review of CXRs was performed by two certified radiologists, ensuring reliable and accurate assessments. Age, gender, and X-ray findings were noted.Results: Among the total of 510 patients included in the study, 463 (90.8%) were male, while 47 (9.2%) were female. The age range of the study population spanned from 12 to 64 years, with the majority falling within the 23-33 year age group. During the review of CXRs, 433 (84.90%) were classified as normal, while 77 (15.10%) were deemed abnormal. The most frequently observed abnormal pattern was ground glass opacification, accounting for 54.5% of the cases, followed by the reticular pattern at 45.5%.Conclusion: CXRs obtained from confirmed COVID-19 patients were normal in 85% of the patients. The most common abnormality seen in our study population was involvement of the lower lobes with patchy peripheral ground glass opacities or reticular shadowing, which was focal or multifocal in location.
Keywords: Chest X-ray; CXR; COVID-19; Ground glass opacities; Lung